2022
DOI: 10.2106/jbjs.21.00746
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship of 4,748 Contemporary Total Ankle Replacements from the French Discharge Records Database

Abstract: Background: Studies of survivorship of primary total ankle replacements (TARs) beyond 5 years have shown varying results among early and modern designs. National cohorts give valuable insights about TAR outcomes, revision risk factors, and specific designs. The purpose of this study was to investigate implant survivorship and risk factors for revision of contemporary TARs using our national database.Methods: This observational study included patients identified in the national PMSI (Programme médicalisé des sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Moreover, many studies that reported no statistically significant risk association between patient age with primary TAA failure tended to be limited in the number of patients included [ 31 , 33 , 34 ]. A recent study on a total of 4748 patients, with 677 patients under the age of 50 years, found that younger age is a significant patient risk factor, which is in agreement with the findings of our study [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, many studies that reported no statistically significant risk association between patient age with primary TAA failure tended to be limited in the number of patients included [ 31 , 33 , 34 ]. A recent study on a total of 4748 patients, with 677 patients under the age of 50 years, found that younger age is a significant patient risk factor, which is in agreement with the findings of our study [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…They also noted that with the use of modern prostheses, survival analysis showed improved results [ 25 ]. Similarly, another study using the French exhaustive discharge database reported a 5-year survival rate of 84% and a 10-year survival rate of 78% [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term and large-scale follow-up of ankle replacement has been further reported, including some of the first available registry data. Using the French Discharge Records Database, Dagneaux et al 39 found survivorship of metal components to be 84% at 5 years and 78% at 10 years. Younger age, second-generation implants, and low institutional volume for the procedure were independent predictors of all-cause revision.…”
Section: Ankle Arthritis and Reconstructionmentioning
confidence: 99%
“…However, Usuelli et al reported greater improvements in patient-reported outcomes (PROs) following TAA in younger patients 10 . Other studies have shown the exact opposite, with higher rates of revision and implant failure in younger cohorts or with younger age being an independent predictor of all-cause revisions [11][12][13] . To date, no clear consensus regarding the association between age and outcomes after TAA has been established.…”
mentioning
confidence: 96%